Physical Exercise as a Strategy for Prevention and Management of Alzheimer’s Disease Progression - Haber, Mateusz; Kula, Paula; Juśkiewicz, Adam; Grelewicz, Olga; Kucy, Natalia; Servaas, Elwira; Czachor, Adrianna; Kotula, Alicja; Siemiątkowski, Robert (Journal of Education, Health and Sport, 2024)
Background: Alzheimer's disease (AD, Alzheimer's Disease) is a chronic, progressive neurodegenerative disease that is a major cause of dementia in the elderly. Current drug therapies have limited effectiveness, prompting the search for alternative and complementary treatments. A growing body of scientific evidence suggests that regular physical activity may play a key role in preventing and slowing the progression of AD by affecting brain fitness Purpose: The purpose of this study is to analyze the available scientific evidence and examine the impact of physical activity on the progression, course and prevention of AD. We analyze how regular exercise may affect cognitive function, brain structure and neurodegenerative biomarkers associated with AD. Material and methods: The review was based on the analysis of materials collected in the databases "Pubmed", Google Scholar, ResearchGate, books and other scientific articles. The search was conducted using keywords: “Alzheimer’s Disease”, “physical activity”, “impact of PA on AD”, “prevention” Results: A review of the literature has shown that regular physical activity can help improve cognitive function and delay the progression of AD through a variety of biological mechanisms, including increased neurogenesis, improved cerebral blood flow and reduced inflammation. Conclusions: The results suggest that regular physical activity may play an important role in the prevention and progression of AD, offering potential cognitive and neuroprotective benefits. These findings the importance of promoting physical activity as a non-pharmacological strategy to counteract AD. Based on these findings, further research should focus on determining the optimal types and intensities of exercise and the mechanisms behind their effects.